AWARE characterization factors in Peru encompassing El Niño and climate change events: does increased water availability guarantee less water scarcity? - Sanchez Matos, J.; Vázquez-Rowe, I.; Kahhat, R. (Springer, 2025)
Water scarcity is a critical environmental challenge which will be exacerbated by the effects of climate change and increased human demand. Hence, more precise and realistic methods of quantifying this impact are necessary. In this sense, the present study proposes updated water scarcity characterization factors (CFs) for watersheds in Peru using the AWARE method. The novelty is linked to the consideration of present and future conditions, as well as quasi-cyclical climatic events such as El Niño.
Keywords: Climate change; Hyper-arid region; Industrial ecology; Life cycle impact assessment; Water scarcity; https://purl.org/pe-repo/ocde/ford#1.05.00